Fruits, vegetables and sweetened beverages dietary patterns among individuals with glucose metabolism disorder - Málaga Chávez, Renzo Mauricio (2021)
Introduction: Little is known about dietary patterns among individuals with type 2 diabetes mellitus (T2DM) in Peru. This study aimed at determining whether there is association between glucosa metabolism disorder and consumption of fruits, vegetables and sweetened beverages. Material and Methods: Secondary analisis of a population-based cross-sectional study conducted in Tumbes, a región in northern Peru. The outcomes variable were consumption of fruits, vegetables and sweetened beverages, defined by self-report, whilst the exposure was glucose metabolism disorder status (euglicemic, with T2DM bit not aware of diagnosis, and with T2DM and aware of diagnosis), defined by the oral glucose tolerance test. To assess the associations of interest, Poisson regression models with robust variance were created, and prevalence ratios (PR) and 95% confidence intervals (95% CI) were reported. Results: A total of 1607 individuals, mean age 48.2 (SD:10.6); and 809 (50.3%) females, was enrolled. The prevalence of T2DM was 11.0% (95%CI: 9.5%-12.6%), and out of them, 105 (59.7%) had previous diagnosis. Only 213 (13.3%) reported consuming sweetened beverages > once/week, whilst 409 (25.5%) and 736 (45.8%) reported consuming vegetables and fruits, respectively. Those with previous T2DM diagnosis had lower probability of consuming sweetened beverages (sometimes vs. never: PR=0.57; 95%CI: 0.41-0.78, and >once/week vs. never PR=0.39; 95%CI: 0.18-0.85). Both the consumption of fruits and vegetables were similar among those with and without previous T2DM diagnosis. Conclusions: Compared to euglycemic subjects, individual with previous T2DM diagnosis had lower consumption of sweetened beverages, but such association was not present among those with T2DM but without previous diagnosis. Fruits and vegetables consumption were not different between the different glucose metabolism disorder categories.